RUMAH ADAT LOPO: TEMPAT BERKUMPUL DAN BELAJAR NILAI PERSAUDARAAN - Tritanty Sintikhe Manu; Hiwa Wonda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The lopo traditional house is a cultural symbol of the Atoin Pah Meto people on Timor Island, rich in social and philosophical values. Lopo is not only a physical gathering place, but also a social learning space that instills the values of brotherhood, mutual cooperation and local democracy. This study aims to explore the fuction and meaning of the Lopo traditional house as a medium for learning the values of brotherhood and its relevance in the context of local cultural education. The study was conduced using a qualitative approach through a literature review of several previous studies. The results of the study indicate that lopo serves as a space of social interaction, a place for deliberation, and an informal educational facility that internalizes the values ​​of unity and togetherness of indigenous communities. These values ​​can be integrated into social studies learning to strengthen students' character and cultural literacy.